# = ln Z

p2
V gs Z 3
−β 2m
=
],
d
p
ln[1
+
ze
(2π¯
h)3
N = z∂ ln Z/∂z
V gs Z 3
1
0
=
dp
p2
3
β 2m
(2π¯
h)
−1
1+z e
E = −∂ ln Z/∂β
1
V gs Z 3 p2
.
=
dp
p2
3
(2π¯
h)
2m 1 + z −1 eβ 2m

βP V

(1)
(2)
(3)
(4)
(5)
(6)

For the case when the integrands depend only on  = p2 /2m we can replace
3√
d3 p by 2π(2m) 2 d .

βP V

3
1
2πV gs (2m) 2 Z
=
d 2 ln[1 + ze−β ] ,
3
(2π¯
h)

(7)

3
1
2πV gs (2m) 2 Z 
2
N =
d
,
(2π¯
h)3
1 + z −1 eβ

(8)

3
3
2πV gs (2m) 2 Z 
2
E =
.
d
(2π¯
h)3
1 + z −1 eβ

(9)

Changing variables to x = β we obtain
βP V

3
1
2πV gs (2mkT ) 2 Z
dxx 2 ln[1 + ze−x ] ,
=
3
(2π¯h)

(10)

3
1
2πV gs (2mkT ) 2 Z
x2
N =
,
dx
(2π¯h)3
1 + z −1 ex

(11)

3
3
Z
x2
2πV gs (2mkT ) 2
E =
kT dx
.
(2π¯h)3
1 + z −1 ex

(12)

With
λ= √

2π¯
h
2πmkT

these can be rewritten as
1
2gs Z
βP = √ 3 dxx 2 ln[1 + ze−x ] ,
πλ

(13)

N/V

1
2gs Z
x2
= √ 3 dx
,
πλ
1 + z −1 ex

(14)

E/V

3
2gs Z
x2
= kT √ 3 dx
.
πλ
1 + z −1 ex

(15)

By writing √ 3 = 2∂x 2 3∂x and integrating by parts in eq (10). fν (z) = (16) eqs. N/V = λ3 2 3gs E/V = kT 3 f 5 (z) . Γ( 52 ) = 34 π). (17). we can show that 2 P = E/V . again.(7-9) take on the form gs P = kT 3 f 5 (z) . follows from wrting √ 3 = 2∂x 2 3∂x and integrating by parts. λ 2 gs f 3 (z) . 2λ 2 Eq. 3 Introducing the functions 1 Z xν−1 dx −1 x . Γ( 23 ) = 21 π . Γ(ν) z e +1 √ √ √ (Γ( 21 ) = π . (17) (18) (19) .